1182. Risk Factors for the Acquisition of IMP-Type Carbapenemase-Producing Carbapenem-Resistant Enterobacteriaceae in Japan: A Matched Case–control Study. (26th November 2018) - Saito, Sho; Hayakawa, Kayoko; Ishikane, Masahiro; Tajima, Taichi; Matsunaga, Nobuaki; Ide, Satoshi; Kinoshita, Noriko; Kusama, Yoshiki; Fujitomo, Yumiko; Nakamoto, Takato; Toda, Yuta; Ohmagari, Norio
Abstract: Background: The majority of CRE in Japan are IMP-type carbapenemase-producing CRE (IMP-CRE). However, research on risk factors for the acquisition of IMP-CRE has been limited, and questions exist regarding whether IMP-CRE have risk factors similar to other types of CRE such as KPC. Methods: We conducted a matched case–control study involving patients from whom IMP-CRE had been isolated. The controls were selected among patients with carbapenem susceptible Enterobacteriaceae (CSE). Non-meropenem-susceptible per CLSI criteria and/or ceftazidime-resistant Enterobacteriaceae were screened, and metallo-β-lactamase–positive isolates were examined for bla IMP by PCR (January 2012 to December 2016). Results: Ninety-six patients with CRE were matched with 96 patients with CSE. They comprised Enterobacter sp. ( n = 132 [CRE: 66, CSE: 66], 68.8%) and Klebsiella pneumoniae ( n = 60 [CRE:30, CSE:30], 31.2%), and bacteria were most commonly isolated from sputum ( n = 76 [39.6%]), followed by urine ( n = 62 [32.3%]). Background factors such as age (median = 75 [IQR: 66–84]), sex (male = 56.8%), and the Charlson comorbidity index (median = 2 [IQR: 1–3.8]) were similar between CRE and CSE. In multivariate analysis, independent risk factors were identified: history of gastrointestinal (GI) endoscopy or surgery, history of ICU stay, and a previous exposure within 1 month to penicillins with β-lactamase inhibitors, cephalosporines, or carbapabnems. Conclusion: Histories of GI endoscopy and ICU stay as well as broad-spectrum antimicrobial exposure were identified as risk factors for CRE isolation. Infection control measures combined with enhanced antimicrobial stewardship are key to preventing the spread of IMP-CRE. Disclosures: All authors: No reported disclosures.